2021
DOI: 10.3389/fmed.2021.634208
|View full text |Cite
|
Sign up to set email alerts
|

Skin Manifestations in COVID-19 Patients: Are They Indicators for Disease Severity? A Systematic Review

Abstract: Introduction: Until now, there are several reports on cutaneous manifestations in COVID-19 patients. However, the link between skin manifestations and the severity of the disease remains debatable. We conducted a systematic review to evaluate the temporal relationship between different types of skin lesions and the severity of COVID-19.Methods: A systematic search was conducted for relevant studies published between January and July 2020 using Pubmed/Medline, Embase, and Web of knowledge. The following keyword… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
104
1
8

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(116 citation statements)
references
References 82 publications
3
104
1
8
Order By: Relevance
“…Thus, skin lesions that precede general symptoms or are even the only sign of positive COVID-19 could serve as early indicators of disease or as indicators of asymptomatic carriers of the virus. In addition, some types of lesions precede the development of the more typical COVID-19 symptomatology and there is even evidence that some types of lesions lead to a worse prognosis and evolution of the disease [25]. This would make it easier therefore to predict a more serious or severe course of SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, skin lesions that precede general symptoms or are even the only sign of positive COVID-19 could serve as early indicators of disease or as indicators of asymptomatic carriers of the virus. In addition, some types of lesions precede the development of the more typical COVID-19 symptomatology and there is even evidence that some types of lesions lead to a worse prognosis and evolution of the disease [25]. This would make it easier therefore to predict a more serious or severe course of SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence supports that herpes zoster might be a cutaneous manifestation of COVID-19 (Brancaccio et al 2021 , Jamshidi et al 2021 ). In this regard, it has been postulated that COVID-19-associated immunosuppression (e.g., suppressed T cell-mediated immunity) or the psychological stress inflicted by the pandemic might promote VZV reactivation and thus account for the escalating number of herpes zoster cases (Pona et al 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…Maculopapular rash was frequently reported in moderate severity with good outcome. Retiform purpura was associated with more severe disease and worse prognosis [ 22 ]. However, from our study, urticaria and maculopapular rash could be observed in any severity of COVID-19 except asymptomatic and had 100% survival rate.…”
Section: Discussionmentioning
confidence: 99%